THE CONVERSATION IMPLICATURE IN PRESIDENT JOKO WIDODO RHETORICAL AND DIPLOMATIC SPEECH - Rangga Asmara; Widya Ratna Kusumaningrum (Universitas Negeri Makassar, 2021)
The paper aims to describe the implicature used by President Joko Widodo in his speech on international forums. This study employs a pragmatic analysis approach to identify the implicative meanings of his speech. The data were the videos and texts of the transcription of President Joko Widodo's speech at the APEC CEO Summit Summit in Beijing on November 10, 2014 and the Asian-African Conference in Jakarta on April 22 2015. The data were analyzed by using note-taking techniques comprising two stages, (1) classifying linguistic data that contains implicatures and (2) interpreting the meaning behind the implicature used, based on the context of the situation and the background of the relevant discourse. Based on the results, President Joko Widodo‘s speech was dominated by several implicatures including influencing, insinuating, convincing, threatening, complaining, clarifying, and governing.